Pembelajaran Matematika Sekolah Dasar: Antara Kepercayaan Vs Realita - Novy Trisnani (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Mathematical myths/beliefs are mental representations or views held by an individual towards mathematics, which may be constructed as a result of social experience, mediated through school, parents, peers or mass media. The purpose of this research is to examine the myths that exist and are believed by people or someone who has been the object of learning mathematics. The research method used in this research is library research/library research. To achieve this goal, this research article is supported by various literatures sourced from journals or scientific articles that discuss topics with keywords: mathematical problems, difficulty analysis, as well as journals that have criteria such as; published in the last five years, and is already indexed. Searching for reference sources resulted in 42 journals or articles consisting of 16 international articles, 28 national journals, and 4 printed books. which is difficult, 3) mathematics is about numbers and abstract objects, 4) mathematics is about right or wrong, 5) learning mathematics is terror anxiety/fear, and 6) math is the same as brain processing.